Pengaruh Persepsi Otentik Pelanggan terhadap Loyalitas Merek pada Resort Kota Batam - Robby Kurniawan; Sharon (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to identify whether there is an impact of authentic perceptions on brand loyalty at resorts in Batam City. The research population is tourists or residents who have stayed at hotels in Batam. The population formed in the findings of this research is all the people of Batam City who have visited resorts in Batam City. Non Probability sampling is a technique used in sampling. The research results interpret that brand awareness is positively influenced by customers' authentic perceptions. The research results also interpret that brand loyalty is positively influenced by perceived quality. The research results also interpret that brand loyalty is positively influenced by brand awareness